2018
DOI: 10.1088/1538-3873/aae916
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Data from KLAWS-2G for an Astronomical Site Survey of Dome A, Antarctica

Abstract: We present an analysis of meteorological data from the second generation of the Kunlun Automated Weather Station (KLAWS-2G) at Dome A, Antarctica during 2015 and 2016. We find that a strong temperature inversion exists for all the elevations up to 14 m that KLAWS-2G can reach, and lasts for more than 10 hours for 50% or more of the time when temperature inversion occurs. The average wind speeds at 4 m elevation are 4.2 m s −1 and 3.8 m s −1 during 2015 and 2016, respectively. The strong temperature inversion a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…With a full-year monitoring in 2011 from KLAWS, Hu et al (2014) found a strong temperature inversion existed for more than 70% of the time above snow surface, and up to 95% above 6 m. The temperature gradient was often greater than 10 • C from 0 m to 10 m. These were further confirmed with 20 month data from KLAWS-2G in 2015 and 2016 (Hu et al 2019).…”
Section: Meteorological Parameters and Boundary Layermentioning
confidence: 62%
See 3 more Smart Citations
“…With a full-year monitoring in 2011 from KLAWS, Hu et al (2014) found a strong temperature inversion existed for more than 70% of the time above snow surface, and up to 95% above 6 m. The temperature gradient was often greater than 10 • C from 0 m to 10 m. These were further confirmed with 20 month data from KLAWS-2G in 2015 and 2016 (Hu et al 2019).…”
Section: Meteorological Parameters and Boundary Layermentioning
confidence: 62%
“…Since katabatic wind dominates the Antarctica continent, the wind speed should be very low in general with random directions at Dome A. These were confirmed and an average wind speed of 1.5 m s −1 was recorded at 4 m in 2011 (Hu et al 2014), but it was about 4 m s −1 in 2015-2016 (Hu et al 2019). They concluded that the difference reflects the annual climatological change.…”
Section: Meteorological Parameters and Boundary Layermentioning
confidence: 87%
See 2 more Smart Citations
“…At Dome A, most of the turbulence integral is contributed by the GL. The wind velocity in this layer is typically quite small, having a yearly average of 3 − 5 m s −1 (Hu et al 2014(Hu et al , 2019. For the AST3 telescopes, and a wind speed of 5 m s −1 , the characteristic time is T0 = 0.3 s. From Fig.…”
Section: Resultsmentioning
confidence: 93%